Infective endocarditis complicating COVID-19 pneumonia: a case report. Issue 6 (7th November 2020) - Spinoni, Enrico Guido; Degiovanni, Anna; Della Corte, Francesco; Patti, Giuseppe
Abstract: Background: During the COVID-19 outbreak, cardiovascular imaging, especially transoesophageal echocardiography (TOE), may expose healthcare personnel to virus contamination and should be performed only if strictly necessary. On the other hand, transthoracic echocardiography (TTE) and TOE represent the first-line imaging exams for the diagnosis of infective endocarditis (IE). To date, this is the first case of COVID-19 complicated by IE. Case summary: We present the case of a 57-year-old man with severe COVID-19 pneumonia requiring mechanical ventilation. During the intensive care unit (ICU) stay, he developed fever and positive haemocoltures for methicillin-resistant Staphylococcus aureus infection. TTE did not identify endocardial vegetations. TOE was then performed and outlined IE of the aortic valve on the non-coronary cusp. Antibiotic therapy was given with progressive resolution of the septic state and improvement of inflammatory signs. After 30 days of ICU stay, the patient was transferred to the Sub-ICU and then to a rehabilitation hospital. A close follow-up has been scheduled: after full recovery, a new echocardiography will be performed (TTE and TOE, if the former is non-conclusive) to consider surgical valve repair in the case of persistence/progression of the valvular lesion or deterioration of the valve function. Discussion: In COVID-19 patients, echocardiography remains the leading imaging exam for the diagnosis of IE. If the suspicion of IE is high, even in this setting of patients, TTE or TOE (if TTE is non-conclusive) are mandatory. A high degree of attention must be paid and appropriate preventive measures taken to avoid contamination of healthcare personnel.